Visual Search, anticipation, and reactive comparisons between highly-skilled and beginning tennis players - Singer, R. N.; Caraugh, J. H.; Steinberg, G. M.; Chen, D.; Frehlich, S. G. (Journal of Applied Sport Psychology, 1996)
Simulated Tennis playing situations were created for the laboratory testing of visual search patterns, anticipation, reactions and movements to compare male and female high-level and beginning players. Of particular interest was the degree to which each measure would differentiate the groups. Participants were highly-rated university players (N=30) and the students enrolled in a beginning tennis class (N=30). Under one testing condition, visual search patterns were recorded as they viewed filmed opponents serve (60 trials) and hit ground strokes (60 trials). Also recorded was anticipation accuracy and speed of the intended type and location of serves and the intended placement of ground strokes. In other testing, execution of a split step was followed by moving rapidly to the correct location for a simulated stroke in response to a series of light cues. Reaction and movement times were recorded. Discriminant analysis revealed that experts and beginners were most differentiated due to fixations on certain cues and predicting ball direction. As to visual search analysis of fixation duration for nine possible areas during the serves, only the head was significant. beginners directed more time toward the head region than did the highly skilled. Experts and novices had similar visual patterns with respect to ground strokes, and a few differences existed within the two female groups, in the two male groups, as well as between males and females. Anticipation measures for the serve indicated that experts were faster and more accurate than beginners, and males were faster than females. Ground stroke data revealed that the highly-skilled were faster and more accurate than novices. Finally, the simulated split-step data showed that reaction times and movement times were faster for the experts versus the beginners, and males were quicker in movements than females.